Handwashing practice among healthcare providers in a teaching hospital in Southern Nigeria - Bello, Segun; Effa, Emmanuel E; Okokon, Enembe E; Oduwole, Olabisi A (International Journal of Infection Control, 2013)
Handwashing is the simplest and most cost-effective intervention to reduce transmission of nosocomial infections. In a cross-sectional descriptive survey, we investigated the practice, knowledge beliefs/attitude and determinants of handwashing among healthcare providers in a teaching hospital in southern Nigeria. A semi-structured, self-administered questionnaire was used to collect data from respondents. Wards and clinical meetings were used as clusters to recruit participants. We found that more than two-thirds of participants had good handwashing practice. Inadequate facilities hindered compliance with handwashing guidelines. Nurses had significantly higher handwash frequency per patient contact than other healthcare providers. Majority (78.5%) of participants knew that hands should be washed for at least 15 seconds, for effective prevention of nosocomial infection. Most (96.3%) respondents believed that handwashing reduces the opportunity of infection transfer from one patient to another. Nurses and respondents who believed that facilities were adequate to prevent infection transmission, were more likely to comply. Provision of adequate facilities could improve handwashing practice. Keywords: handwashing, infection control, healthcare providers, guidelines, intervention, prevention